(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Social media create a virtual word. It means Media is an instrument on communication, like a newspaper, TV or a radio, so social media would be a social instrument of communication. Really social media play a very crucial role in social media world. We see variety of people on new media world. We have freedom to categories them, freedom to pick up and choose them as our friend, as we do in our real life. But there is a big difference; we do not actually meet them. Nevertheless, these virtual people provide us with the platform where we can, without any hesitation, share our feelings, which otherwise we would not have discussed face to face. Social media is a 5th pillar, a potent one, which through the help of technology helps in the creation and dissemination of information. More ever, in today’s fast new media world, we have paucity of time; these social media communication tools furnish us with flexibility of time. It describes websites that allow users to share content, media, etc. The social media study comprised a sample of 250 respondents from Delhi-NCR (including 130 from the NCR region of Delhi), Based upon the opinions and beliefs of the public, as revealed by the study. The methodology used in the research work is convenience sampling. The data has been collected personally with the help of a well structured and non disguised questionnaire. Common examples are the popular social networking sites like Friendster, Facebook, MySpace, Digg, Twitter, YouTube, photo-bucket, flicker and Wikipedia etc. But these communication tools have profoundly changed our lives and how we interact with one another and the world around us.